Transcriptome analysis of adenomyosis eutopic endometrium reveals molecular mechanisms involved in adenomyosis-related implantation failure and pregnancy disorders - Elena Juárez-Barber; Ana Corachán; María Cristina Carbajo-García; Amparo Faus; Carmen Vidal; Juan Giles; Antonio Pellicer; Irene Cervelló; Hortensia Ferrero (BMC, 2024)
Abstract Background Women with adenomyosis are characterized by having defective decidualization, impaired endometrial receptivity and/or embryo-maternal communication, and implantation failure. However, the molecular mechanisms underlying adenomyosis-related infertility remain unknown, mainly because of the restricted accessibility and the difficult preservation of endometrial tissue in vitro. We have recently shown that adenomyosis patient-derived endometrial organoids, maintain disease-specific features while differentiated into mid-secretory and gestational endometrial phase, overcoming these research barriers and providing a robust platform to study adenomyosis pathogenesis and the associated molecular dysregulation related to implantation and pregnancy disorders. For this reason, we aim to characterize the dysregulated mechanisms in the mid-secretory and gestational endometrium of patients with adenomyosis by RNA-sequencing. Methods Endometrial organoids were derived from endometrial biopsies collected in the proliferative phase of women with adenomyosis (ADENO) or healthy oocyte donors (CONTROL) (n = 15/group) and differentiated into mid-secretory (-SECorg) and gestational (-GESTorg) phases in vitro. Following RNA-sequencing, the significantly differentially expressed genes (DEGs) (FDR < 0.05) were identified and selected for subsequent functional enrichment analysis and QIAGEN Ingenuity Pathway Analysis (IPA). Statistical differences in gene expression were evaluated with the Student's t-test or Wilcoxon test. Results We identified 1,430 DEGs in ADENO-SECorg and 1,999 DEGs in ADENO-GESTorg. In ADENO-SECorg, upregulated genes included OLFM1, FXYD5, and RUNX2, which are involved in impaired endometrial receptivity and implantation failure, while downregulated genes included RRM2, SOSTDC1, and CHAC2 implicated in recurrent implantation failure. In ADENO-GESTorg, upregulated CXCL14 and CYP24A1 and downregulated PGR were related to pregnancy loss. IPA predicted a significant inhibition of ID1 signaling, histamine degradation, and activation of HMGB1 and Senescence pathways, which are related to implantation failure. Alternatively, IPA predicted an inhibition of D-myo-inositol biosynthesis and VEGF signaling, and upregulation of Rho pathway, which are related to pregnancy loss and preeclampsia. Conclusions Identifying dysregulated molecular mechanisms in mid-secretory and gestational endometrium of adenomyosis women contributes to the understanding of adenomyosis-related implantation failure and/or pregnancy disorders revealing potential therapeutic targets. Following experimental validation of our transcriptomic and in silico findings, our differentiated adenomyosis patient-derived organoids have the potential to provide a reliable platform for drug discovery, development, and personalized drug screening for affected patients.